(untitled) (International Journal of Engineering and Computer Science, 2015)
Neural Network most probably known as ”Artificial Neural Network (ANN)” is an information processing model, that is analogous to the way the biological nervous systems processes information. Neural networks can be used to extract patterns and detect trends that are too complex to notice by either humans or other computer techniques. In today’s network world, maintaining the security of information or physical property is becoming both increasingly important and difficult. From time to time we hear about the crimes of Credit Card Fraud, Computer break in by hackers or security breach in a company or government buildings. In most of these crimes, the criminals were taking advantages of a fundamental flaw in the conventional access control systems. The systems do not grant access to “ Who we are ”, but give details about “ What we have ”, such as ID cards, keys, passwords, PIN numbers, or mother’s and maiden name. None of these mean are not really define us but rather they merely authenticate us. It goes without saying that if someone steals, duplicates, or acquire these identity then, he or she will be able to access our data or our personal property anytime they want. Recently, developed technology became available to allow verification of “true” individual identity. This technology is based on a field called “BIOMETRICS” with Neural Networks.